1987
DOI: 10.1073/pnas.84.9.2960
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of cDNA clones encoding the human carcinoembryonic antigen reveal a highly conserved repeating structure.

Abstract: For the isolation of cDNA clones encoding the carcinoembryonic antigen (CEA), we have constructed a cDNA library from human colon tumor mRNA. The library was screened with various oligonucleotides whose sequence had been deduced from partial amino acid sequence data for CEA. Positive candidate clones were hybridized with a probe for repetitive DNA, because CEA mRNA contains anAlu repetitive element, and with a fragment of a genomic clone of nonspecific cross-reacting antigen, an antigen closely related to CEA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
61
0

Year Published

1989
1989
1994
1994

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(62 citation statements)
references
References 35 publications
1
61
0
Order By: Relevance
“…Southern analyses indicated the existence of 9-11 genes in humans (Thompson et al 1987). Sequencing ofgenomic and cDNA clones has revealed the complete primary protein structure of CEA (Beauchemin et al 1987;Oikawa et al 1987c;Zimmermann et al 1987), NCA (Oikawa et al 1987b;Thompson et al 1987;Neumaier et al 1988;Tawaragi et al 1988), and a pregnancy-specific /31 glycoprotein (PS/~G) (Watanabe and Chou 1988a). The highly conserved domains shared by each are a 34-amino-acid leader peptide, a 108-110-amino-acid N-terminal domain, a 178-180-amino-acid repeating unit of which three copies are present in CEA, whereas only one and a half can be found in PSBG and one in NCA, and a 26-aminoacid carboxyl region (CEA) that is 2 amino acids shorter in NCA and degenerate in PSI3G.…”
Section: Introductionmentioning
confidence: 99%
“…Southern analyses indicated the existence of 9-11 genes in humans (Thompson et al 1987). Sequencing ofgenomic and cDNA clones has revealed the complete primary protein structure of CEA (Beauchemin et al 1987;Oikawa et al 1987c;Zimmermann et al 1987), NCA (Oikawa et al 1987b;Thompson et al 1987;Neumaier et al 1988;Tawaragi et al 1988), and a pregnancy-specific /31 glycoprotein (PS/~G) (Watanabe and Chou 1988a). The highly conserved domains shared by each are a 34-amino-acid leader peptide, a 108-110-amino-acid N-terminal domain, a 178-180-amino-acid repeating unit of which three copies are present in CEA, whereas only one and a half can be found in PSBG and one in NCA, and a 26-aminoacid carboxyl region (CEA) that is 2 amino acids shorter in NCA and degenerate in PSI3G.…”
Section: Introductionmentioning
confidence: 99%
“…The mRNAs encoding these antigens show distinct and rather restricted expression patterns, being predominantly found in coIonic mucosa and adenocarcinomas (CEA, NCA), liver (BGP), and cells of the myeloid lineage [NCA, CGM6 (Zimmermann et al 1987Hinoda et al 1990)]. The human CEA-related antigens are encoded by a gene family with -20 members (reviewed in Thompson et al 1991), which represents a branch of the immunoglobulin gene superfamily (Williams and Barclay 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Although it lacks absolute tumour specificity because of the presence of a member of immunologically closely related antigens, such as nonspecific crossreacting antigen (NCA) (von Kleist et al, 1972;Mach & Pusztaszeri, 1972), CEA has been used as an important clinical tumour marker (Tate, 1982). By molecular cloning of cDNA and genomic sequences, primary structures of CEA and NCA were deduced, and revealed that CEA (Oikawa et al, 1987a;Zimmermann et al, 1987;Kamarck et al, 1987;Beauchemin et al, 1987) and NCA (Oikawa et al, 1987b;Tawaragi et al, 1988;Neumaier et al, 1988) have quite similar nucleotide sequences and structures which belong to the immunoglobulin superfamily (Oikawa et al, 1987c;Paxton et al, 1987). The cell surface expression of CEA has been shown to be that of a phosphatidylinositol glycan (PI-G) anchored protein (Hefta et al, 1988;Takami et al, 1988;Hefta et al, 1990), which was cleaved by phosphatidylinositol-specific phospholipase C (PI-PLC) (Ikezawa et al, 1983) similar to Thy-I molecule (Low & Kincade, 1985), the most primitive molecule in the immunoglobulin superfamily.…”
mentioning
confidence: 99%